THE EFFECTIVENESS OF TEACHING CAREER TECHNICAL EDUCATION TO SECONDARY STUDENTS AND ITS IMPACT ON CAREER DEVELOPMENT - Mahan, Travis (Acta Scientiae et Intellectus, 2024)
This paper explores five recently published articles that report on the results of the effectiveness of teaching Career and Technical Education (CTE) to secondary students and the impact that it has on their career development. These five articles have been chosen for their very distinct different views on the effectiveness of teaching CTE to secondary students and the impact that it has on their careers. This paper will explore these distinct views in order to come to a conclusion as to what effective teaching skills work to encourage students to be motivated to continue in the career path that they have stated, or become interested in that field. It is imperative that CTE teachers are versed in multiple disciplines and therefore are more active in a student’s development. A CTE course should not be a class that the school just places a student in order to fill a gap. It is known that this happens, and the instructor must be able to connect with the student, and have a positive impact on that student